A Weak Simpson Method for a Class of Stochastic Differential Equations - Adhikari, Ram Sharan (International Journal of Operational Research/Nepal, 2023)
This paper proposes a novel weak Simpson method for numerical solution for a class of stochastic differential equations. We show that such a method has weak convergence of order one in general and weak convergence of order three under certain additional assumptions, which improves the weak convergence order of two for the weak trapezoid method developed in (1). The main results are illustrated with numerical examples.